Dialects of the Germans of Russia and Kazakhstan - Elena A. Shlegel (Журнал Фронтирных Исследований, 2023)
The linguistic diversity of the Germans in Russia and Kazakhstan is due to the migration of ethnic groups to the territory of the Russian Empire from the lands of Germany and subsequent migrations within the country. Some ethnic Germans use the dialect in speech, for them it is their native language, the rest of the Germans speak literary German to varying degrees, and Russian is considered their native language. Today, it is impossible to uniquely identify one native language for an ethnic group, as Germans speak different dialects of German. The purpose of the study is to determine the states of the modern dialect language of the Germans of Russia and Kazakhstan, to consider how dialects were historically spread throughout the country, and how dialects are preserved now. The article considers the territorial distribution of dialects in Russia, primarily Siberia, where the majority of Germans live, as well as the circulation of German dialects in Kazakhstan after the deportation of Germans. The central part of the article is devoted to the modern state of dialects, which are preserved primarily in places of compact settlement of Germans. The article makes use of the results of ethno-sociological surveys of Germans in Russia and Kazakhstan on the issues of dialects, and analyzes contemporary methods of preserving and translating the language. Conclusions: dialects are preserved where Germans live compactly. The author notes that there are negative trends in the process of preserving dialects, but German public organizations today solve many problems concerning dialects.